Codzienne i duchowe ścieżki kobiet Środkowego Wschodu- Nepalki, Tybetanki i Bhutanki - Skrzypińska, Katarzyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
Diversity, which is characteristic feature of Middle Asia, attracts attention of tourists, adventures’ seekers, scientists and others. It is so fascinating to compare the three countries – such dissimilar as Nepal, Tibet and Bhutan. The article presents everyday and spiritual life of the people and especially women from these countries, on the religious – Hindu and Buddhist – background. Katarzyna Skrzypińska, Uniwersytet Gdański, Instytut Psychologii, ul. Bażyńskiego 4, 80-952 Gdańsk, Poland.